Pengetahuan dan Persepsi Guru Terhadap Pelaksanaan ISO 9000 di Sekolah - Hadi, Mat Dain (1998)
The purpose of this study was to get an information about teachers’ knowledge of IS0 9000 and to see whether their knowledge and demographic factors affect their perceptions towards implementing IS0 9000 in schools. The study was done using a Systematic Sampling Techniques by choosing 340 respondents from 10 schools in Temerloh district Pahang Darul Makmur. The respondents represent 75.2% of the total teachers population in the district. A set of questionnaires containing questions regarding demographics, knowledge and perception factors were distributed to each of the respondent for he or she to decide on one answer. All data were processed using a computer program called SPSS 7.5. Hypotheses testing techniques were used to compare variables for significant differences and to identify significant relationship between variables. Results shown that there were no significant differences of demographic factors such as gender, age, teaching experience and school location on the perception of teachers towards implementing IS0 9000 in schools. Teachers’ knowledge of IS0 9000 has a very significant relationship with their perception on implementing of IS0 9000 in school.